The Principal’s Role and Islamic Education Learning at Muhammadiyah Elementary School during the Covid-19 Pandemic - Lukman Asha (STAI Hubbulwathan Duri, 2021)
The purpose of this study was to examine the principal's managerial role in ensuring that learning processes at Muhammadiyah primary school continue desirably and effectively during the Covid-19 pandemic. Additionally, this study intended to depict learning processes in Islamic education. The principal and six Islamic education instructors were purposefully chosen as informants in this investigation. The data were gathered via documentation, observation, and interviews in order to ensure the data's credibility. Following the data collection and analysis was conducted using an interactive model. This study established that, during the covid19 epidemic, the principal used a combination of remote and face-to-face learning as a manager. Certain classes are held online and offline learning as scheduled one at a time on specific days. Through the use of such a learning system, processes and activities for instilling students' religious, moral, and social values may be conducted. Apart from offline learning, the principal and teachers collaborated with students' parents to supervise students' or children's learning processes at home. To preserve the quality of teachers, the principal encouraged teachers to participate in training on creating learning films as an engaging medium for students to comprehend the contents presented during class readily.